National Family Health Survey-3 reported low full-immunization coverage rates in Andhra Pradesh, India: who is to be blamed? - Chandran, S. Anil; Ramachandra, Srikrishna S.; Sekhar, P. Satya (Journal of Public Health, 2011)
Background National Family Health Surveys (NFHS), the Indian counterpart of Demographic and Health Surveys, are the most recognized surveys in India and provide reliable measures of RCH indicators. But NFHS-3 figures on full immunization coverage rate for the state of Andhra Pradesh (AP) is very low compared with seven other major surveys on immunization carried out around the same time period. Methods The objective is to analyse factors responsible for low full-immunization coverage rate reported by NFHS-3 in AP. Data from three waves of NFHS and other surveys on immunization were used for analysis. Results Although full immunization coverage rate did not increase, other related indicators have shown an improvement between the second and third waves of NFHS. The full immunization coverage rate was significantly higher among card seen category as compared with card not seen category. Conclusions Low full immunization coverage rate in AP as reported by NFHS-3, in all likelihood cannot be totally attributed to poor performance of the immunization programme. Probable reasons are issues related to methodological and logistic processes in NFHS, which include collection of data from a wider age group, differences in data collection methods, commitment levels and skill sets of investigator, fatigue factor and low percentage of cards seen by investigator.